PENGARUH PENDEKATAN KONTEKSTUAL TERHADAP HASIL BELAJAR SISWA DALAM PKn KELAS III SDN SE-PONTIANAK KOTA - Natalia,Mastar, Dominika; Asran, Mastar; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Â AbstractThe problem in this research is "How is the influence of applying contextual approach to student learning outcomes in civic education learning in class III State Elementary School 42 Pontianak City?". This research uses experimental method of quasi-experimental type with experimental design of Non-Equivalent Control Group Design. The population of all students in grade III of Pontianak City State Elementary School who are accredited A and still use KTSP. Samples of students of class III D (experiment) amounted to 25 students and III C (control) amounted to 25 students. The research instruments are 50 multiple choice test. Technique of data collection using measurement technique and direct observation. The result of data processing is obtained by mean of pre-test of control class 58,44 and mean experiment class pre-test 57,9. While the average post-test control class 69.42 and the average post-test experimental class 75.26. Hypothesis test using t-test (Polled Variance) obtained tcount = 2,8740 for dk = 48 and Î± = 5% obtained t_table equal to 1.6749, mean t_hitung> t_table (2.8740> 1.6749), then Ha accepted. So, it can be concluded there is influence of student learning outcomes that apply contextual approach. The result of calculation effect size (ES), obtained by 0.57 (medium criterion). This means that the application of a contextual approach to civic education learning provides a moderate impact on the outcomes of third grade students of State Elementary School 42 Pontianak City.Keywords: Influence, Contextual Approach, Learning Outcomes